EFFECTIVE COMMUNICATION WITHIN THE COACHING STAFF ROUNDTABLE - Itoudis, Dimitris; Báder, Márton; Vitutti, Francesco (Sport- és Egészségtudományi füzetek, 2026)
The round table discussion started with a thought-provoking question from Prof. Dr. Sc Igor Jukić, the moderator wondered what the participating professionals expected when they moved to a new team as an active player or coach. Márton Báder thinks that a player definitely has to be conscious or realistic about his/her level and always has to look for the next step, but money should not be the primary consideration. During his career, when it came to changing teams, the coach was very important. He pointed out that the Euroleague standards are very high at the moment, as is the way players are treated.